2017
DOI: 10.24323/akademik-gida.345258
|View full text |Cite
|
Sign up to set email alerts
|

Isıl İşlem Görmüş İçme Sütlerinde (Pastörize, UHT ve Laktozsuz UHT Süt) Hidroksimetilfurfural İçeriğinin Belirlenmesi

Abstract: Maillard reaction (non-enzymatic browning) formed during heat treatment is an important for the quality of foods. Hydroxymethylfurfural (HMF) is an intermediate compound of this reaction and can be changed with temperature during production and storage in dairy products. In this study, the HMF levels of pasteurized and UHT milks with different fat contents were determined. In addition to the effect of hydrolisation of lactose on HMF contents, the composition and colour values of milk samples were also determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
2
0
2
Order By: Relevance
“…The differences in HMF values observed from the initial heating processes may be due to brand differences in the milk used. In a study, the HMF content of whole, semi-skimmed, and skimmed milk from different brands were in the range of 4.90±0.27-12.74±0.63, 2.50±0.30-8.89±0.18, 2.16±0.37-7.49±0.11 µM/L, respectively (25). In another study, the total HMF content of commercial UHT and sterilized milk samples with different fat content was in the range of 3.46-5.75 µM/L and 15.52-21.38 µM/L, respectively (14).…”
Section: Discussionmentioning
confidence: 99%
“…The differences in HMF values observed from the initial heating processes may be due to brand differences in the milk used. In a study, the HMF content of whole, semi-skimmed, and skimmed milk from different brands were in the range of 4.90±0.27-12.74±0.63, 2.50±0.30-8.89±0.18, 2.16±0.37-7.49±0.11 µM/L, respectively (25). In another study, the total HMF content of commercial UHT and sterilized milk samples with different fat content was in the range of 3.46-5.75 µM/L and 15.52-21.38 µM/L, respectively (14).…”
Section: Discussionmentioning
confidence: 99%
“…The initial HMF content of UHT milk groups significantly affects HMF content after the ohmic process. A study conducted by Urgu et al (2017) showed that the HMF content of full-fat, semi-skimmed and skimmed UHT milk belonging to different brands was in the range of 315-1606 ng/µL. Morales and Jiménez--Pérez (1999) also stated that the total HMF content of commercial UHT milk samples with different fat contents was in the range of 436-725 ng/µL.…”
Section: Discussionmentioning
confidence: 99%
“…Çiğ süte, patojen mikroorganizmalar ile normal depolama koşullarında süt ve süt ürünlerinde bozulmaya neden olabilecek mikroorganizmaların inhibe edilmesi ve çeşitli enzimlerin kısmen veya tamamen inaktif hale getirilmesi için ısıl işlem uygulanmaktadır. Süt endüstrisinde kullanılan başlıca ısıl işlem uygulamaları pastörizasyon, sterilizasyon ve termizasyon olarak sıralanabilmektedir [1]. Süt işleme tesislerinde söz konusu ısıl işlem uygulamaları, ısı değiştirici veya eşanjör adı verilen, farklı sıcaklıklardaki iki ya da daha çok akışkanın ısılarının birinden diğerine aktarılmasını sağlayan cihazlarda gerçekleşmektedir.…”
Section: Introductionunclassified